OsteoBLAST: Computational Routine of Global Molecular Analysis Applied to Biomaterials Development - Ferreira, Marcel Rodrigues [UNESP]; Milani, Renato; Rangel, Elidiane C. [UNESP]; Peppelenbosch, Maikel; Zambuzzi, Willian [UNESP] (Frontiers, 2020)
For bone purposes, surface modifications are a common trend in biomaterials research aiming to reduce the time necessary for osteointegration, culminating in faster recovery of patients. In this scenario, analysis of intracellular signaling pathways have emerged as an important and reliable strategy to predict biological responses from in vitro approaches. We have combined global analysis of intracellular protein phosphorylation, systems biology and bioinformatics into an early biomaterial analysis routine called OsteoBLAST. We employed the routine as follows: the PamChip tyrosine kinase assay was applied to mesenchymal stem cells grown on three distinct titanium surfaces: machined, dual acid-etched and nanoHA. Then, OsteoBLAST was able to identify the most reliable spots to further obtain the differential kinome profile and finally to allow a comparison among the different surfaces. Thereafter, NetworKIN, STRING, and Cytoscape were used to build and analyze a supramolecular protein-protein interaction network, and DAVID tools identified biological signatures in the differential kinome for each surface.
Keywords: alternative methods; analysis; bioinformatics; biomaterials; bone healing